A Hierarchical Tin/Carbon Composite as an Anode for Lithium‐Ion Batteries with a Long Cycle Life1. Issue 5 (10th December 2014) - Huang, Xingkang; Cui, Shumao; Chang, Jingbo; Hallac, Peter B.; Fell, Christopher R.; Luo, Yanting; Metz, Bernhard; Jiang, Junwei; Hurley, Patrick T.; Chen, Junhong
Abstract Tin is a promising anode candidate for next‐generation lithium‐ion batteries with a high energy density, but suffers from the huge volume change (ca. 260 %) upon lithiation. To address this issue, here we report a new hierarchical tin/carbon composite in which some of the nanosized Sn particles are anchored on the tips of carbon nanotubes (CNTs) that are rooted on the exterior surfaces of micro‐sized hollow carbon cubes while other Sn nanoparticles are encapsulated in hollow carbon cubes. Such a hierarchical structure possesses a robust framework with rich voids, which allows Sn to alleviate its mechanical strain without forming cracks and pulverization upon lithiation/de‐lithiation. As a result, the Sn/C composite exhibits an excellent cyclic performance, namely, retaining a capacity of 537 mAh g−1 for around 1000 cycles without obvious decay at a high current density of 3000 mA g−1.